Remodeling of RecG Helicase at the DNA Replication Fork by SSB Protein - Sun, Zhiqiang (Sci Rep, 2015)
The RecG DNA helicase a key player in stalled replication fork rescue. The single-stranded DNA binding protein (SSB) participates in this process, but its role in the interaction of RecG with the fork remains unclear. We used atomic force microscopy (AFM) to visualize the interaction of RecG with a fork DNA in the presence of SSB. We discovered that SSB enhances RecG loading efficiency onto the DNA fork by threefold. Additionally, SSB interacts with RecG leading to the RecG remodeling. As a result, RecG separates from the fork, but remains bound to the DNA duplex. Moreover, in this new binding mode RecG is capable of translocation along the parental duplex DNA. We propose a model of RecG interaction with the replication fork involving two RecG binding modes. SSB plays the role of a remodeling factor defining the mode of RecG binding to the fork mediated by the SSB C-terminus. In the translocating mode, RecG remains in the vicinity of the fork and is capable of initiating the fork regression. Our results afford novel mechanistic insights into RecG interaction with the replication fork and provide the basis for further structural studies.